A survey of load balancing in distributed systems. (18th March 2020) - Semmoud, Abderraziq; Hakem, Mourad; Benmammar, Badr
With the technological progress, distributed systems are widely used for parallel processing of computationally intensive applications with heterogeneous computing needs. Such environments require effective load balancing (LB) strategies that consider both algorithmic and architectural constraints. Indeed, the efficient load balancing of applications is crucial in order to reach high performance in parallel and distributed systems. By and large, the objective of load balancing is to find a judicious and suitable workload distribution in order to reduce as much as possible the load difference between the computational resources of the network. The proposed work presents a rigorous survey of the relevant existing load balancing techniques in several types of distributed systems. A detailed classification, the strengths and weaknesses of these techniques have been investigated according to the general characteristics of the underlying systems. We also present the main issues and features of fault tolerance and reliability for load balancing in distributed systems.